2014
DOI: 10.1007/s00408-014-9566-9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Limitation in IPF Patients: A Randomized Trial of Pulmonary Rehabilitation

Abstract: Pulmonary rehabilitation effectively maintained exercise oxygen uptake over 3 months and lengthened constant load exercise time in patients with moderately severe IPF. Exercise endurance on cycle ergometry testing was limited by dyspnea and severe hypoxemia associated with systemic oxidant stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 41 publications
3
88
2
3
Order By: Relevance
“…a 100-s or 33% improvement was reached in 30 (91%) out of 33 and 27 (82%) out of 33 investigations, respectively) (figure 1). tLIM is also responsive to rehabilitation in idiopathic PAH [121,122] and IPF [123,124]. In one observational study of 53 IPF patients, the effect size for tLIM after rehabilitation was larger than for V′O 2 peak, WRpeak, 6MWD and ISWT [123] (table 3).…”
Section: Discussionmentioning
confidence: 98%
“…a 100-s or 33% improvement was reached in 30 (91%) out of 33 and 27 (82%) out of 33 investigations, respectively) (figure 1). tLIM is also responsive to rehabilitation in idiopathic PAH [121,122] and IPF [123,124]. In one observational study of 53 IPF patients, the effect size for tLIM after rehabilitation was larger than for V′O 2 peak, WRpeak, 6MWD and ISWT [123] (table 3).…”
Section: Discussionmentioning
confidence: 98%
“…In COPD; chronic hypoxemia has been associated with increased muscle oxidative stress at rest and exercise compared to non-hypoxemic individuals [63] Individuals with non-IIM; particularly idiopathic pulmonary fibrosis (IPF); can exhibit significant hypoxemia; and evidence of oxidative stress has been recently examined in this population (e.g. increased plasma 15-F2t0 isoprostanes) [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…There was also evidence of Type II muscle fibre atrophy on muscle biopsy in IIM. Alterations in muscle metabolism were reported in three studies and included decreased muscle oxygen extraction with exercise; and evidence of oxidant stress and lipid peroxidation in IPF [25,26,28] (Table 3). Oxidative enzyme concentrations or activity were not reported.…”
Section: Alterations In Peripheral Muscle Structure and Metabolic Chamentioning
confidence: 99%
“…30 The long-term effects of PR within this population group are uncertain and a recent study by Jackson et al found that while IPF patients allocated PR showed improvements in quality of life and physical activity, these changes were only noted for the duration of the intervention and not three months later. 31 The lack of sustained improvements may in part reflect the progressive nature of the disease but it is also possible that the rehabilitation needs of some IPF patients differ from those with other chronic lung diseases, with disease severity playing an important part in treatment response. As recommended by the NICE guidelines, further trials are required involving IPF patients with differing disease severities to look at the effect of both short-and longterm outcomes.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%